Bioavailability of Different Vitamin D Oral Supplements in Laboratory Animal Model - Egidijus Šimoliūnas; Ieva Rinkūnaitė; Živilė Bukelskienė; Virginija Bukelskienė (Medicina, 2019)
Background and Objectives: The major cause of vitamin D deficiency is inadequate exposure to sunlight. It is difficult to supplement it with food because sufficient concentrations of vitamin D naturally occur only in a handful of food products. Thereby, deficiency of this vitamin is commonly corrected with oral supplements. Different supplement delivery systems for improved vitamin D stability and bioavailability are proposed. In this study, we compared efficiency of three vitamin D delivery systems: microencapsulated, micellized, and oil-based. Materials and Methods: As a model in this medical testing, laboratory rats were used for the evaluation of bioavailability of different vitamin D vehicles. Animals were divided into three groups: the first one was given microencapsulated vitamin D3, the second—oil-based vitamin D3, and the third—micellized vitamin D3. Test substances were given per os to each animal for 7 days, and vitamin D concentration in a form of 25-hydroxyvitamin D (25(OH)D) in the blood was checked both during the vitamin delivery period and later, up to the 24th day. Results: Comparison of all three tested products showed that the microencapsulated and oil-based vitamin D3 vehicles were the most bioavailable in comparison to micellized vitamin D3. Even more, the effect of the microencapsulated form of vitamin D3 remained constant for the longest period (up to 14 days). Conclusions: The results of this study suggest that the oral vitamin D supplement vehicle has an impact on its bioavailability, thus it is important to take into account how much of the suppled vitamin D will be absorbed. To maximize the full exploit of supplement, the best delivery strategy should be employed. In our study, the microencapsulated form of vitamin D was the most bioavailable.